EXPANDING ACCESS TO FINANCIAL SERVICES IN RURAL AREAS OF IRAQ: TOWARDS COMPREHENSIVE FINANCIAL INCLUSION - Asst. Prof. Ali Abdulkadhim Dadoosh (Scholar Express Journals, 2025)
The study aims to shed light on the (positive and negative) impacts of financial inclusion in Iraq, particularly in rural areas. It examines key indicators of financial inclusion, namely outreach and usage indicators, which measure the volume of loans and deposits relative to GDP. Additionally, it studies the density and spread of bank branches, ATMs, and electronic payment services (POS) (POC). Despite some developments and a relative improvement in the financial inclusion rate, which exceeded 40% by the end of 2024, the overall data remains significantly weak compared to neighboring and regional countries. The study concludes that expanding access to financial services in rural areas of Iraq is a top priority for both the government and the private sector. This requires joint cooperation among all stakeholders, which contributes to enhancing economic and social growth in those areas. Consequently, the study proposes general and specific strategies to address the challenges of weak financial inclusion in the country. The most important of these include revitalizing infrastructure, increasing community awareness, and providing and diversifying financial services, in addition to the necessity of promoting financial inclusion in rural areas of Iraq due to its significant importance in boosting economic growth in the country and thus achieving comprehensive financial inclusion in Iraq
Keywords: Financial Inclusion; Iraqi Economy; Financial and Banking Depth